Guest

(1/5) ÷ (5/6) = (1/5) (6/5) (1/5) ÷ (5/6) = (1/5) (6/5)

 (1/5) ÷ (5/6) = (1/5)                                      (6/5)
 (1/5) ÷ (5/6) = (1/5)                                      (6/5)

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Dear Student

1/5) ÷ (5/6) = (1/5) × (6/5)
While dividing one fraction by another fraction, we multiply the first fraction by the reciprocal of the other.


Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free